The Problem Of Vocational And Pedagogical Training Of Future History Teachers - Israilov Qobiljon Toshtemirovich (Zien Journals, 2022)
In this scientific article, the state of professional-pedagogical perception of future history teachers in the educational process, professional-pedagogical perception, its criteria, professional-pedagogical-analytical thinking, perception-analysis, as well as the process of teaching at the University and paying attention to teaching history to students in extracurricular activities, determining the level and objectives of teachers ' appeals to historical works; the results of finding out that they are provided with the necessary literature and methodology, theoretical and practical bases of improving the professional training of students of higher educational institutions are covered
Keywords: professional-pedagogical perception; professional-pedagogical-analytical thinking; perception-analysis; practical